2004
DOI: 10.1536/jhj.45.823
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stable Outcome in Treating Chronic Heart Failure Patients With Carvedilol

Abstract: SUMMARYCarverdilol has a variable outcome in treating patients with chronic heart failure. This prospective single-center study evaluated the predictors of clinical variables in determining favorable outcomes in treating chronic heart failure patients with carvedilol. The relation between clinical variables and maintenance doses of carvedilol was also determined.Seventy chronic heart failure patients (mean age, 62.2 years, 50 males and 20 females) with a left ventricular ejection fraction < 35% and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition, genetic differences in the responses to BBs have also been suggested as the reason for the small dose among Japanese, 11) however, there is a report that 25 mg of carvedilol was well tolerated among Chinese who might be considered to be genetically similar to Japanese. 12) There is anecdotal experience in which carvedilol was used at a dose above 20 mg daily in Japan, 13) but the report was limited to 5 patients receiving ventricular assist devices. Fur-thermore, we reported a case that showed significant left ventricular reverse remodeling (LVRR) after the titration of 40 mg/day of carvedilol under the pacing of cardiac resynchronization therapy (CRT).…”
mentioning
confidence: 99%
“…In addition, genetic differences in the responses to BBs have also been suggested as the reason for the small dose among Japanese, 11) however, there is a report that 25 mg of carvedilol was well tolerated among Chinese who might be considered to be genetically similar to Japanese. 12) There is anecdotal experience in which carvedilol was used at a dose above 20 mg daily in Japan, 13) but the report was limited to 5 patients receiving ventricular assist devices. Fur-thermore, we reported a case that showed significant left ventricular reverse remodeling (LVRR) after the titration of 40 mg/day of carvedilol under the pacing of cardiac resynchronization therapy (CRT).…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Carvedilol is an antihypertensive agent which possesses both alpha 1 and beta-receptor blocking properties. [8][9][10][11] In this study, our objective was to evaluate the effects of carvedilol versus atenolol and doxazosin on metabolic parameters in hypertensive patients with MetS.…”
mentioning
confidence: 99%
“…Investigation in humans suggests that carvedilol administration is effective in advanced disease (ie, EF ,25% 4,5 ) as well as in very elderly patients 28 ; however, one report indicated that response was suboptimal in patients with larger heart sizes, worse systolic function, and more advanced clinical heart failure class. 29 Advanced canine DCM is accom- panied by progressive myocyte loss due to necrosis, apoptosis, atrophy, and fibrous or fatty infiltration. 30,31 The remaining myocytes demonstrate significant abnormalities of transcription of basic cellular components as well as deficiencies in mitochondrial protein expression.…”
Section: Discussionmentioning
confidence: 99%